A new copper complex on graphene oxide: A heterogeneous catalyst for N‐arylation and C‐H activation. (26th November 2019) - Mittal, Ayushi; Kumari, Shweta; Parmanand,; Yadav, Deepak; Sharma, Sunil K.
Abstract : Graphene oxide supported Cu (II) ligand complex (GO@AP/L‐Cu) has been synthesized and characterized by FT‐IR, Raman, PXRD, UV–Visible, TGA, XPS, FESEM, TEM, EDAX, Elemental mapping, BET, CHNS and AAS analysis. The complex has been found to be efficient and reusable heterogeneous catalyst for the N ‐arylation and C‐H activation reactions, both the catalytic reactions were found to be simple, cleaner and give high yields (~ 90%) of product. The catalyst can be easily filtered out from the reaction mixture and reused up to four times without significant loss of catalytic activity. The reported method is economical and novel in the sense that aqueous medium was used for both the reactions and for the stability of the catalyst. All isolated organic products were fully characterized on the basis of their physical and spectral data. Abstract : Graphene oxide supported Cu(II) ligand complex (GO@AP/L‐Cu) has been synthesized and found to be efficient and recyclable heterogeneous catalyst for the N‐arylation and C‐H activation reactions.